Constructionof Security of Monitoring Platform in Electric Power Dispatching Internal Network - Lin Yuan; Xiasheng Gao; Tianhong Zhao (Dianxin kexue)
Power dispatching internal network contains of a large amount of safety equipments, but lacks of centralized monitoring, statistical analyzing and unified managing tool. A platform for monitoring the security of electric power dispatching internal network was constructed. The platform acquires realtime security equipments operating status, alarms, and logs information, through standardized data processing, analysis and calculation, to achieve centralized monitoring, integrated alarm, hidden danger reminder, statistical analysis, report generation and decision functions.